Metabolic Disruption as a Clinical Early Warning Signal: a Review of Systems Metabolite Flux Analysis - Ahmed, Waleed Khalid; Fayyad, Mohammed Amer; Attawi, Jamal A. AL-Jabbar (American Journal of Biomedicine and Pharmacy, 2026)
This review aims to consider the use of systemic metabolite flux analysis as a sensitive methodology for diagnosing early metabolic disturbance in clinical practice. In contrast to traditional static biomarker measurements, metabolic flux analysis quantifies real-time metabolite flow through biochemical pathways, providing information about physiological dysfunction. The review investigates such methodological methods as isotopic tracer methods with a special focus on ¹³C metabolic flux analysis (¹³C-MFA), and constraint-based modelling. Oncology, metabolic disorders, and neurodegenerative diseases exhibit evidence that flux variations are antecedent to, or significantly ahead of, conventional diagnostic markers in time. Technical barriers are also discussed in the review, and, as future solutions, a translational framework for the clinical application of flux-based diagnostics as a warning system.